Modern View on Enterococcus faecalis and Enterococcus faecium Resistance Mechanisms to Antibiotics - T. S. Komenkova; E. A. Zaitseva (Антибиотики и Химиотерапия)
Enterococci are currently becoming one of the major causative agents of various infectious diseases. Enterococcus faecalis and E.faecium are the most common species causing enterococcal infections. Both species exhibit natural low-level resistance to aminoglycosides, cephalosporins, quinolones, clindamycin, and co-trimoxazole. In addition, the peculiarities of their genome make it easy to acquire resistance to other antibiotics widely used in clinical practice, through mutations or by horizontal gene transfer. The review represents current knowledge about the mechanisms of enterococcal resistance to the most commonly used antibiotics.